Chemoradiotherapy of newly diagnosed glioblastoma with intensified temozolomide - Weiler, Markus; Hartmann, Christian; Wiewrodt, Dorothee; Herrlinger, Ulrich; Gorlia, Thierry; Bähr, Oliver; Meyermann, Richard; Bamberg, Michael; Tatagiba, Marcos; Deimling, Andreas von; Weller, Michael; Wick, Wolfgang (International journal of radiation oncology, biology, physics, 2010)
To evaluate the toxicity and efficacy of chemoradiotherapy with temozolomide (TMZ) administered in an intensified 1-week on/1-week off schedule plus indomethacin in patients with newly diagnosed glioblastoma.
Online veröffentlicht am 14. Oktober 2009
Gesehen am 19.10.2023